Evaluasi Layanan Teknologi Informasi ITIL Versi 3 Domain Service Desain pada Universitas Selamat Sri Kendal - Herlinudinkhaji, Didin (Walisongo Journal of Information Technology, 2019)
Information technology is a necessity for companies and organizations. To ensure the continuity of information technology business processes, it is also very necessary that companies get added value for their use. ITIL v3 is a method used to designing, ensure value is met, provide quality services, and ensure that the parts run as desired. Service design is used to assist companies in designing infrastructure, architecture, service quality, policies, and documents IT. ITIL v3 domain service design in this study is also used as a basis for developing information technology usage policies.